2001
DOI: 10.1346/ccmn.2001.0490601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Crystal Chemistry of Oxidation in Annite: Resolving the Hydrogen-Loss and Vacancy Reactions

Abstract: Abstract--A synthetic octahedral-site-vacancy-free annite sample and its progressive oxidation, induced by heating in air, were studied by powder X-ray diffraction (pXRD), M6ssbauer spectroscopy, nuclear reaction analysis (NRA), Raman spectroscopy, X-ray fluorescence (XRF) spectroscopy, gas cba-omatography (GC), thennogravimetric analysis (TGA), differential thermal analysis (DTA), scanning electron microscopy (SEM), and size-fraction separation methods. For a set heating time and as temperature is increased, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 71 publications
(101 reference statements)
3
27
1
Order By: Relevance
“…The broad distribution with an average field of 43-44 T was assigned to goethite of lower crystallinity. This assignment is consistent with Ranourt et al (23) who assigned a distribution of HFDs in annite samples to a mixture of hematite and poorly crystalline Fe oxides. The decrease in the intensity of the broad component after the bioreduction indicated that the poorly crystalline fraction of goethite was preferentially reduced by the bacteria.…”
Section: Resultssupporting
confidence: 91%
“…The broad distribution with an average field of 43-44 T was assigned to goethite of lower crystallinity. This assignment is consistent with Ranourt et al (23) who assigned a distribution of HFDs in annite samples to a mixture of hematite and poorly crystalline Fe oxides. The decrease in the intensity of the broad component after the bioreduction indicated that the poorly crystalline fraction of goethite was preferentially reduced by the bacteria.…”
Section: Resultssupporting
confidence: 91%
“…Mossbauer data were collected at the Department of Physics, Ottawa University, employing the techniques described by Rancourt et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…These calculations are relatively insensitive to various assumptions regarding the energetics of, or the precise amount of this small amount of oxyannite component, the substitution mechanisms of which have been studied in detail by Rancourt et al (2001).…”
Section: M1mentioning
confidence: 99%
“…In annite, for example, the ideal end-member stoichiometry * E-mail: dgr@physics.uottawa.ca K(Fe 2+ 3 )(AlSi 3 )O 10 (OH) 2 is never attained because of mismatch constraints between the larger VI (Fe 2+ 3 ) octahedral and smaller IV (AlSi 3 ) tetrahedral sheets, which require some Fe 3+ to be present even under highly reducing conditions (Hazen and Wones 1972;Redhammer et al 1993;Rancourt et al 1994aRancourt et al , 2001Mercier et al 1996Mercier et al , 1999. The latter situation is believed to occur from the geometrical limit of !…”
Section: +mentioning
confidence: 99%
“…Because accurate Fe-site populations were required, all folded raw spectra were corrected for thickness effects as described previously (Rancourt 1989(Rancourt , 1998Rancourt et al 1994aRancourt et al , 1994bRancourt et al , 2001. To treat thickness effects properly, each raw spectrum was Þ rst Þ tted with an arbitrary number of Voigt lines to obtain a statistically ideal Þ t. Intrinsic absorber cross-sections were then extracted from the Voigt Þ ts and used to generate thin-limit spectra (TLS) that are completely corrected for absorber thickness effects, both spectral shape and relative and absolute intensities.…”
Section: Iron Site Populations From Mössbauer Spectroscopymentioning
confidence: 99%